OP0197 THE INITIAL TREATMENT OF SYSTEMIC JUVENILE IDIOPATHIC ARTHRITIS: AN INTERNATIONAL COLLABORATION AMONG 10 REGISTRIES. (2nd June 2020) - Son, M. B.; Kimura, Y.; Aalto, K.; Berntson, L.; Dallas, J.; Duffy, C.; Glerup, M.; Guzman, J.; Herlin, T.; Hovi, P.; Hyrich, K.; Klotsche, J.; et al.
Abstract : Background: The introduction of biologics has transformed care for children with systemic juvenile idiopathic arthritis (SJIA). Differences in treatment approaches between countries and how they have changed over time are not well studied. Objectives: We contrast the initial features, treatment and 12-month outcome in SJIA across 10 JIA registers in Europe and North America. Methods: Data were extracted locally from 10 Registers including manifestations at diagnosis, medication use over first year and outcomes (Physician Global Assessment (PGA), active joint count (AJC)) at 12 months. Data was compared before/after 2012 to assess change over time. Weighted (w) means were used to adjust for varying number of patients/Register. Results: 1, 149 patients; 553 had medication data for 2012-2018; primarily female and Caucasian; median age at diagnosis 5.3-8 years. Median duration of symptoms prior to first visit varied (0-3.3 months). Glucocorticoid (GC) use was common in the first year (w_average 72% (range 33-96%)). Biologic use included IL-1, IL-6 and TNF inhibitors. The proportion of patients treated with biologics, primarily anakinra, increased after 2012 (Table 1 ). W_mean PGA and AJC at the 12±3 month visit were 1.55 and 1.57, respectively (Table 2 ). At one year, the proportion of patients prescribed GC varied (w_mean 40%, range 26-60%). Conclusion: Analysis of SJIA patients across 10 countries show that time to first rheumatology visit was highly variable. Although local factors influence treatment decisions, biologic use increased after 2011; anakinra most common. Nearly 75% of patients were prescribed steroids within the first year but seemed to decrease after 1 year. More study is needed on long-term outcomes in SJIA patients within this modern era. Disclosure of Interests: Mary Beth Son: None declared, Yukiko Kimura Consultant of: Genetech, Kristiina Aalto: None declared, Lillemor Berntson: None declared, Johnathan Dallas: None declared, Ciaran Duffy: None declared, Mia Glerup: None declared, Jaime Guzman: None declared, Troels Herlin: None declared, Petteri Hovi: None declared, Kimme Hyrich Grant/research support from: Pfizer, UCB, BMS, Speakers bureau: Abbvie, Jens Klotsche: None declared, Bo Magnusson: None declared, Vanessa McItyre: None declared, Ellen Nordal: None declared, Seza Özen: None declared, Maria Jose Santos Speakers bureau: Novartis and Pfizer, Betül Sözeri: None declared, Timothy Beukelman Consultant of: UCB, Novartis